Re-thinking Mobility Poverty Understanding Users' Geographies, Backgrounds and Aptitudes - Kuttler, Tobias; Moraglio, Massimo (Transport and Society, 2021)
"This book seeks to better conceptualise and define mobility poverty, addressing both its geographies and socio-economic landscapes. It moves beyond the analysis of 'transport poverty' and innovatively explores mobility inequalities and social construction of mobility disadvantages. The debate on mobility poverty is gaining momentum due to its role in triggering social exclusion and economic deprivation. In this light, this book examines the social construction of mobility poverty by delving into mobility patterns and needs as they are differently experienced by social groups in different geographical situations. It considers factors such as the role of transport regimes and their social value when analysing the social construction of individual´s mobility needs. Furthermore, the gaps between articulated and unarticulated needs are identified by observing actual travel patterns of individuals. The book offers a comparison of the global phenomenon through fieldwork conducted in six different European countries - Greece, Portugal, Italy, Luxembourg, Romania and Germany. This book will be useful reading for planners, sociologists, geographers, mobility/transport researchers, mobility advocates, policy-makers and transport practitioners. The Open Access version of this book, available at https://doi.org/10.4324/9780367333317, has been made available under a Creative Commons Attribution 4.0 license."